Time truncated efficient testing strategy for Pareto distribution of the 2nd kind using weighted poisson and poisson distribution - Mughal, Abdur Razzaque; Zakiyah Zain,; Nazrina Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this study, group acceptance sampling plan (GASP) proposed by Aslam et al. (2011) is redesigned where the lifetime of test items are following Pareto distribution of 2nd kind. The optimal plan parameters are found by considering various pre-determined designed parameters. The plan parameters were obtained using the optimization solution and it also concludes that the proposed plan is more efficient than the existing plan as it requires minimum sample size.